Analisis Peningkatan Kompetensi, Pelatihan, dan Motivasi Terhadap Kinerja Karyawan (Studi Pada Perusahaan Daerah Air Minum Surakarta) - Kukuh Purbo Marjiyanto; Zakky Fahma Auliya (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTThis study aims to determine the effect of competence, training, and motivation on employee performance (a case study of a Surakarta municipal water company). This type of research is quantitative. This research uses primary data. The sample in this study were 112 respondents taken from Surakarta regional water company (PDAM) employees who had competence in their fields, and had received training and motivation from the company. The sampling technique uses simple purposive. Data collection method using a questionnaire. The results showed that competency had a significant effect on the performance as evidenced by the t value of 4.381; a significance value of 0,000 <0.05. The training did not significantly influence the performance as evidenced by the t value of 1.232; a significance value of 0.221> 0.05. Motivation has a significant effect on the performance as evidenced by the t value of 3.074; significance value 0.003 <0.05.